Genetic and linguistic evolution and coevolution - Hunley, Keith (Henry Stewart Talks, 2015)
The first study of global gene-language coevolution, Coevolution since 1988, Coevolution in the genomic era, Serial Founder Effect for genes and languages?, Regional studies of language and population genetic evolution